Ready for Transfer to Adult Care? A Triadic Evaluation of Transition Readiness in Adolescents With Congenital Heart Disease and Their Parents. (August 2019) - Burström, Åsa; Acuña Mora, Mariela; Öjmyr-Joelsson, Maria; Sparud-Lundin, Carina; Rydberg, Annika; Hanseus, Katarina; Frenckner, Björn; Nisell, Margret; Moons, Philip; Bratt, Ewa-Lena
Transfer to adult care for adolescents with chronic conditions ought to be determined by transition readiness. The aims of this study were (a) to describe the level of readiness for transition in adolescents with congenital heart disease, (b) to compare adolescents' assessment of transition readiness with their parents' assessments, and (c) to study potential correlates of transition readiness. A total of 157 triads of adolescents aged 14 to 18 years and their parents completed the Readiness for Transition Questionnaire. Adolescents scored higher on overall readiness than their parents. Multivariable analyses revealed that higher levels of adolescents' overall readiness were associated with a less threatening view of the illness, a higher level of empowerment, and with higher mothers' and fathers' overall readiness scores. Adolescents' responsibility scores were positively associated with age and parental adolescent responsibility scores. Parental involvement scores were negatively associated with adolescents' age and positively with the mothers' parental involvement scores. By using a triadic evaluation, the results of the present study significantly extend what is currently known about this population.